Peningkatan Hasil Belajar Peserta Didik pada Pembelajaran Pendidikan Pancasila dengan Menggunakan Model Cooperative Learning Tipe Two Stay Two Stray di Kelas V Sdn 16 Kampeh Kabupaten Agam - Nur Hafizah; Masniladevi; Yarisda Ningsih; Yullys Helsa (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
The purpose of this study is to describe the improvement of students' learning outcomes in Pancasila Education learning through the use of the Two Stay Two Stray Cooperative Learning model in class V of SDN 16 Kampeh, Agam Regency. This study is a Classroom Action Research (CAR) with qualitative and quantitative approaches. The research subjects consisted of 13 students, including 6 boys and 7 girls. Data collection techniques were carried out through observation, learning outcome tests, and documentation. Qualitative data were analyzed through data reduction, data presentation, and drawing conclusions, while quantitative data were analyzed using percentage calculations and average values ​​to see the improvement in each cycle. The results showed an improvement in various aspects. The value of the teaching module increased from 89.58% (B) in cycle I to 95.83% (SB) in cycle II. The activity of teachers and students also increased from 88.75% (B) to 97.5% (SB). In addition, student learning outcomes increased from an average of 79.35 (C) in cycle I to 88.74 (B) in cycle II. Thus, it can be concluded that the application of the Two Stay Two Stray type Cooperative Learning model can improve students' learning outcomes in Pancasila Education learning in class V of SDN 16 Kampeh, Agam Regency.